1998
DOI: 10.1038/26989
|View full text |Cite
|
Sign up to set email alerts
|

The Xenopus Wnt effector XTcf-3 interacts with Groucho-related transcriptional repressors

Abstract: Tcf/Lef transcription factors mediate signalling from Wingless/Wnt proteins by recruiting Armadillo/beta-catenin as a transcriptional co-activator. However, studies of Drosophila, Xenopus and Caenorhabditis elegans have indicated that Tcf factors may also be transcriptional repressors. Here we show that Tcf factors physically interact with members of the Groucho family of transcriptional repressors. In transient transfection assays, the Xenopus Groucho homologue XGrg-4 inhibited activation of transcription of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
516
3
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 616 publications
(536 citation statements)
references
References 29 publications
10
516
3
3
Order By: Relevance
“…Whether Grg5 is directly controlling the expression levels of Ihh or whether it has a more indirect role, is not known. We note, however, that Grg5, in contrast to other Grgs, is the only molecule among five Drosophila gro homologues in vertebrates that is not a repressor, but a positive regulator (Roose et al, 1998;Brantjes et al, 2001). Furthermore, we have preliminary data to support the idea that Grg5 is a coactivator of the transcription factor Cbfa1/Runx2.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Whether Grg5 is directly controlling the expression levels of Ihh or whether it has a more indirect role, is not known. We note, however, that Grg5, in contrast to other Grgs, is the only molecule among five Drosophila gro homologues in vertebrates that is not a repressor, but a positive regulator (Roose et al, 1998;Brantjes et al, 2001). Furthermore, we have preliminary data to support the idea that Grg5 is a coactivator of the transcription factor Cbfa1/Runx2.…”
Section: Discussionmentioning
confidence: 65%
“…Members of the other subgroup, e.g., Grg5 in mice and AES in humans, contain the amino-terminal region of gro, including the Q-rich domain, but lack most of the variable region and the entire WD-40 repeat region. Mammalian gro homologues in the first group bind to transcription factors that target gene repression (Aronson et al, 1997;Roose et al, 1998;Eberhard et al, 2000;Tetsuka et al, 2000;Wang et al, 2000;Brantjes et al, 2001), whereas the short form of gro, such as XGrg5 in Xenopus, has been shown to enhance transcriptional activity (Roose et al, 1998;Brantjes et al, 2001). It has been speculated that Grg5 may act as a dominant negative molecule within a transcription complex.…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of TLE in modulating Tcf4-dependent Wnt activity is controversial. A mouse TLE homolog does not bind to mouse Tcf4 in a yeast 2-hybrid assay, 57 and mouse and human Tcf4 share 98% amino acid homology; 58 however, a more recent study has demonstrated that TLE co-repressors could inhibit the transcriptional activity of all Tcf factors. 59 Further study is necessary to delineate the role, if any, of TLE factors in the de-repression of Wnt activity in butyrate-treated HCT-116 cells.…”
Section: Discussionmentioning
confidence: 96%
“…Among other activities, "fulllength" Grgs can act to repress the transcription of Wnt target genes (Cavallo et al, 1998;Roose et al, 1998;Brantjes et al, 2001). The pattern of Grg gene expression suggested that Grgs are not induced by BMP to inhibit Wnt responses in the interfollicular spaces, but rather that they might be induced downstream of ␤-catenin signaling to provide negative feedback on this signal transduction pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptional repressor activity, shared by Grgs 1-4, is mediated by a carboxyl terminal domain that is absent in Grg5 and the Grg3b isoform (Mallo et al, 1995;Leon and Lobe, 1997;Roose et al, 1998;Brantjes et al, 2001;Muhr et al, 2001). Grg5 can competitively inhibit the repressive activity of the fulllength Grg isoforms Brantjes et al, 2001;Muhr et al, 2001).…”
Section: Introductionmentioning
confidence: 99%